A comprehensive review of mycoviruses infecting the plant pathogenic fungus Rosellinia necatrix - Hassan, Sidra; Coutts, Robert H. A.; Jamal, Atif; Kotta-Loizou, Ioly (Frontiers in Virology, 2025)
The number of documented viruses that infect fungi has increased during the past few decades. Mycoviruses that infect plant pathogenic fungi are the main focus of mycoviral research since some of them have the capacity to cause hypovirulence to their host and hence function as potential biocontrol agents. This article provides a comprehensive overview of mycoviruses infecting plant pathogenic fungus Rosellinia necatrix causing white root rot, including the prevalence of their occurrence, their taxonomic classification, their genomic organization and structure, impacts on their fungal host in terms of phenotype in general and virulence in particular, and their ecological interactions including transmission. The white root rot fungus is found to harbor diverse mycoviruses with double-stranded and positive-sense single-stranded RNA genomes from different families, including Spinareoviridae, Megabirnaviridae, Partitiviridae, Quadriviridae, Pseudototiviridae, Endornaviridae, Fusariviridae, Yadokariviridae, Hypoviridae, Fusagraviridae and Megatotiviridae. Some of these mycoviruses studied in R. necatrix or a heterologous host Cryphonectria parasitica revealed interesting virus-host interplays and appear to be promising agents for biological control applications against white root rot.